Far from the madding crowd [videorecording (DVD)] - Mulligan, Carey, 1985-; Sheen, Michael; Schoenaerts, Matthias, 1977-; Sturridge, Tom; Hardy, Thomas, 1840-1928 (Twentieth Century Fox Home Entertainment, 2015)
Based on the literary classic by Thomas Hardy about Bathsheba Everdene who is an independent woman who attracts three different suitors: a sheep farmer; a dashing soldier; and a prosperous, older bachelor. This timeless story of Bathsheba's passions explores the nature of relationships, love and resilience.